2011
DOI: 10.1590/s0034-71672011000200004
|View full text |Cite
|
Sign up to set email alerts
|

Eventos adversos relacionados a medicamentos: percepção de técnicos e auxiliares de enfermagem

Abstract: The process of administering medication is linked to an elevated rate of adverse events and has been the focus of institutional investments. This study aimed at uncovering the perception of nursing aides regarding medication-related adverse events. A qualitative research was carried out with ten nursing aides from a clinical and surgical inpatient unit in a university hospital in Porto Alegre,RS, Brazil. Results show that the factors most commonly involved in medication errors are work overload and incorrect p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
22

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 13 publications
(15 reference statements)
1
15
0
22
Order By: Relevance
“…These situations may increase the odds of adverse events. This is consistent with past studies (18)(19) that have shown excessive workload to be a significant driver of adverse events and human error due to haste.…”
Section: Discussionsupporting
confidence: 92%
“…These situations may increase the odds of adverse events. This is consistent with past studies (18)(19) that have shown excessive workload to be a significant driver of adverse events and human error due to haste.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study identified the practice of informal communication and the omission of adverse events among professionals in hospital practice (17) . The perception and conduct of professionals in relation to errors may vary according to the institutional culture (punitive or not) (18) , and is also closely related to individual responsibility (19)(20) . Thus, it is important to invest in disseminating safety culture with an emphasis on education and communication, adopting conducts based on protocols, guidelines and SOPs, expanding safety knowledge according to the perspective of continuous construction, taking into account the reality of the institution and also the meanings and values that the professionals attribute to patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Os erros com maior destaque na literatura estão relacionados diretamente com a equipe de enfermagem, pois sua origem está justamente no final do processo de administração de medicamentos, são eles os erros de horário e de velocidade de infusão (11,12,18,20,23,26,(29)(30)(31)(32)38) . Além do fato de terem ênfase nos estudos, esses erros chamam a atenção pelo desfecho que se inicia na falha da terapêutica até o óbito do paciente.…”
Section: Discussionunclassified
“…A seguir foram descriminados os achados em relação aos autores e títulos dos artigos. Análise de causa raiz de incidentes relacionados à segurança do paciente na assistência de enfermagem em unidades de internação, de um hospital privado, no interior do Estado de São Paulo DALMOLIN (12) Erros de medicação no ambiente hospitalar: uma abordagem através da bioética complexa FONTANA, et al (13) Análise documental da mídia escrita sobre eventos adversos ocorridos na prática da enfermagem LOPES, et al (14) Análise da rotulagem de medicamentos semelhantes: potenciais erros de medicação ROQUE; MELO (15) Avaliação dos eventos adversos a medicamentos no contexto hospitalar BOHOMOL (16) Erros de medicação: estudo descritivo das classes dos medicamentos e medicamentos de alta vigilância BELELA; PEDREIRA; PETERLINI (17) Erros de medicação em pediatria CORBELLINI, et al (18) Eventos adversos relacionados a medicamentos: percepção de técnicos e auxiliares de enfermagem VELOSO; TELLES FILHO; DURÃO (19) Identificação e análise de erros no preparo de medicamentos em uma unidade pediátrica hospitalar YAMAMOTO; PETERLINI; BOHOMOL (20) Notificação espontânea de erros de medicação em hospital universitário pediátrico PICHLER, et al (21) Erros de medicação: análise ergonômica de utensílios da sala de medicação em ambiente hospitalar PARANAGUÁ, et al (22) Prevalência e fatores associados aos incidentes relacionados à medicação em pacientes cirúrgicos CAMERINI; SILVA (23) Segurança do paciente: análise do preparo de medicação intravenosa em hospital da rede sentinela LORENZINI; SANTI; BÁO (24) Segurança do paciente: análise dos incidentes notificados em um hospital do sul do Brasil HARADA, et al (25) Segurança na administração de medicamentos em pediatria SILVA; CAMERINI (26) Análise da administração de medicamentos intravenosos em hospital da rede sentinela TEIXEIRA; CASSIANI (27) Análise de causa raiz de acidentes por quedas e erros de medicação em hospital ROZENFEL; GIORDANI; COELHO (28) Eventos adversos a medicamentos em hospital terciário: estudo piloto com rastreadores SILVA; CASSIANI (29) Análise prospectiva de risco do processo de administração de medicamentos antiinfecciosos LOPES, et al (30) Erros de medicação realizados pelo técnico de enfermagem na UTI: contextualização da problemática SILVA, et al (31) Eventos adversos a medicamentos em um hospital sentinela do Estado de Goiás, Brasil LEMOS; SILVA; MARTINE (32) Fatores que predispõem à distração da equipe de enfermagem durante o preparo e a administração de medicamentos PRAXEDES; TELLES...…”
Section: Características Dos Estudos Encontradosunclassified